PENGARUH PENERAPAN METODE PEMBELAJARAN GUIDED DISCOVERY TERHADAP KETERAMPILAN PROSES SAINS SISWA KELAS X SMA NEGERI 1 TERAS BOYOLALI TAHUN PELAJARAN 2011/2012 - Aan Ilmi, Abrari Nur; Indrowati, Meti; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? The purpose of this study is to determine the influence of Guided Discovery learning methods toward science process skill in class X of SMA Negeri 1 Teras Boyolali in academic year 2011/2012. This research was quasi experiment and posttest only control group design was used as a research design. Guided Discovery learning method was independent variables and science skill process was dependent variable. Student of class X of SMA Negeri 1 Teras Boyolali as a population. The samples of this research were the students of class X-1 as the experimental group and students of class X-3 as the control group. The sample of this research was established by cluster random sampling. Data was collected using test and observation. The data were analyzed using t-test method. The conclusion of this research was Guided Discovery learning method was had significantly affected the science process skill on X grade of SMA Negeri 1 Teras Boyolali. Keywords: Guided Discovery learning method, Science Process Skill